The Impact of the Implementation of the Minister of Agriculture Regulation No. 15 of 2021 on Income Rice Milling Unit (RMU) in Tabanan Regency - Kusumawardhani, Sang Ayu Made Ary; Paramarta, Pande Made Ari Ananta (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The aim of this study is to assess the impact of the implementation of Minister of Agriculture Regulation No. 15 of 2021 on the income of rice milling units (RMUs) in Tabanan Regency. The study was conducted in Tabanan Regency because it is the district with the highest rice farming productivity in Bali Province, amounting to 160,000 tons per year. The population for this study is 550 business units. The sample size was determined using the Slovin formula. Based on that population, a sample of 85 rice milling units (RMUs) was obtained. The result of this study shows that Minister of Agriculture Regulation No. 15 of 2021 concerning business activity standards and product standards in the rice milling sector has a significant impact on the economic performance of Rice Milling Units (RMUs) in Tabanan Regency. The implementation of the standards stipulated in the regulation not only focuses on improving product quality but also includes better business management, which directly affects efficiency and productivity. The recommendations from this study include increased dissemination and training for RMU entrepreneurs, provision of access to financing for technology investments, and periodic evaluation and updating of the standards.